From “obligated embeddedness” to “obligated Chineseness”? Bargaining processes and evolution of international automotive firms in China's New Energy Vehicle sector - Julian Schwabe (Growth and Change, 2020)
Over the past decades, the automotive sector in China has been characterized by the obligation of foreign manufacturers to enter joint ventures, transfer technologies, and localize production. Still, the Chinese automotive industry has remained dependent on foreign brands, capital, and technology. The advent of markets and supply chains for electric vehicles, however, changes the framework conditions for established foreign automotive firms in terms of competitive landscape and access to core technology components. This is mainly the result of political initiatives: Established automotive manufacturers are exposed to direct and indirect restrictions that influence their production of electric vehicles, their choice of suppliers, and their potential market shares in the future. This paper outlines multilevel bargaining processes of Chinese and foreign actors as they aim to maximize value capture in a fundamentally transitioning automotive sector. In contrast to the lead firm-centric focus of recent global production networks (GPN)-discussions, this paper argues that the determinants of how production networks evolve is first and foremost a question of the institutional environment. Focusing on power balances between state and firm actors in multilevel bargaining processes offers a way of explaining GPN-evolution in institutional contexts in which power concentrates in executive bodies and decision-making processes are often informal.
Keywords: 300